2016
DOI: 10.1080/09540261.2016.1210103
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to support recovery after domestic and sexual violence in primary care

Abstract: Experiences of domestic and sexual violence are common in patients attending primary care. Most often they are not identified due to barriers to asking by health practitioners and disclosure by patients. Women are more likely than men to experience such violence and present with mental and physical health symptoms to health practitioners. If identified through screening or case finding as experiencing violence they need to be supported to recover from these traumas. This paper draws on systematic reviews publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 69 publications
0
48
0
2
Order By: Relevance
“…Adicionalmente, se encontraron estrategias, como la regulación emocional bajo la supresión y la ree-valuación (Hong et al, 2018), al igual que la identificación de estrategias de control para intervenir en el proceso de lesión (Hartney & Barnard, 2015), la intervención en atención primaria (Hegarty, Tarzia, Hooker, & Taft, 2016), el enfoque integrado de cuerpo, mente y espíritu (Liao, 2019), el empoderamiento y el papel de la comunidad (Inman & Rao, 2018;, la comunicación madres e hijos para romper la vif (Insetta et al, 2015), las intervenciones que construyen el capital social y la capacidad de recuperación de los jóvenes (Scorgie, et al, 2017) y la empatía frente a las historias de superhéroes como fuente de intervención en jóvenes (Weschenfelder, Fradkin, & Yunes, 2018).…”
Section: Total 74unclassified
“…Adicionalmente, se encontraron estrategias, como la regulación emocional bajo la supresión y la ree-valuación (Hong et al, 2018), al igual que la identificación de estrategias de control para intervenir en el proceso de lesión (Hartney & Barnard, 2015), la intervención en atención primaria (Hegarty, Tarzia, Hooker, & Taft, 2016), el enfoque integrado de cuerpo, mente y espíritu (Liao, 2019), el empoderamiento y el papel de la comunidad (Inman & Rao, 2018;, la comunicación madres e hijos para romper la vif (Insetta et al, 2015), las intervenciones que construyen el capital social y la capacidad de recuperación de los jóvenes (Scorgie, et al, 2017) y la empatía frente a las historias de superhéroes como fuente de intervención en jóvenes (Weschenfelder, Fradkin, & Yunes, 2018).…”
Section: Total 74unclassified
“…Social stigma regarding GBV can be so high that affected women are at risk of further violence or abandonment if they disclose the violence [ 5 ], and this can impede women’s seeking of assistance [ 6 ]. Accordingly, multiple agencies recommend integrating care of women who have experienced GBV into general health services to safely reach a maximum number of affected women [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Before-and-after and pilot studies of cognitive behavioural therapies and advocacy interventions have suggested improved psychological outcomes, but require testing in randomized controlled trials. Hegarty, Tarzia, Hooker, and Taft (2016) report similar challenges with regards to primary care responses to domestic violence and highlight a range of potentially promising advocacy, safety planning, and psychological interventions. INTERNATIONAL REVIEW OF PSYCHIATRY, 2016VOL.…”
Section: Editorialmentioning
confidence: 99%
“…Previous work has suggested that mental disorder is associated with an increased risk of domestic violence perpetration, although it is unknown whether a causal relationship exists (Oram, Trevillion, Khalifeh, Feder, & Howard, 2014). Yet, and as highlighted by Hegarty et al (2016) and Trevillion et al (2016) with regards to primary and secondary care settings, respectively, there is a critical lack of evidence for interventions to reduce domestic violence perpetration (Hegarty et al, 2016;Trevillion et al, 2016). Easton and Crane (2016) take on this issue in the final paper of the volume.…”
Section: Editorialmentioning
confidence: 99%